Assessing the diagnostic accuracy of biochemical, anthropometric, and combined indices for metabolic syndrome prediction in a cohort from Qatar Biobank - Muhammad Ammar Zahid; Abrar Abdelrahman; Hicham Raïq; Abdelhamid Kerkadi; Abdelali Agouni (PLoS ONE, 2025)
Introduction Metabolic syndrome (MetS) poses a substantial health risk, particularly in Qatar. This study aimed to compare the diagnostic accuracy of various indices for MetS identification in a well-characterized Qatari cohort from Qatar Biobank (QBB). Methods This cross-sectional study included 692 adults (≥18 years) from the QBB, categorized into MetS and healthy groups using the International Diabetes Federation (IDF) criteria. We compared the distributions of biochemical, anthropometric, and combined indices between groups. Logistic regression assessed associations with MetS, adjusting for demographics. Receiver Operating Characteristic (ROC) analysis evaluated discriminative performance and identified optimal thresholds. Robustness was tested using a 75/25 train-test split. Stratified analyses examined the influence of age, gender, and nationality. Results The MetS prevalence was 19.1% among participants. Individuals with MetS displayed significantly higher levels of all indices compared to the healthy group. Triglycerides (adjusted odd ratio (AOR): 4.93), waist circumference (AOR: 3.87), and lipid accumulation product (LAP) (AOR: 14.91) showed the strongest associations within their respective categories. LAP achieved the highest discriminative performance (area under the curve (AUC): 0.896; 95% CI: 0.870–0.923), followed by the visceral adiposity index (VAI) (AUC: 0.877) and TyG × waist circumference (AUC: 0.872). LAP’s optimal threshold was 37.1, with a sensitivity of 0.856 and a specificity of 0.789. Combined indices consistently outperformed individual measures. Discriminative accuracy was comparable across genders and nationalities but higher in individuals under 45 years. Conclusion Combined indices, particularly LAP, demonstrate superior discriminative ability for MetS in this Qatari cohort. Incorporating LAP into routine clinical practice could improve MetS detection and facilitate timely interventions. Further validation in larger, diverse populations is, however, warranted.